Neuromuscular Disorders in Pregnancy - Edmundson, Christyn; Guidon, Amanda C. (Seminars in Neurology, 2017)
Neuromuscular disorders may present and progress differently in women than in men. During pregnancy, medication adjustment, hormonal effects, and other alterations in physiology may influence the manifestation of a variety of neuromuscular disorders. The expression of existing conditions may change; previously asymptomatic conditions may be unmasked, or entirely new conditions may develop. Additionally, neuromuscular disorders and their treatments may have implications for the fetus. Such factors must be carefully considered when counseling and treating pregnant women and those considering pregnancy. This article reviews considerations specific to women and issues surrounding pregnancy in disorders of the neuromuscular junction, focal neuropathies, and acquired and inherited disorders of the nerve and muscle.
Keywords: neuromuscular disease; pregnancy; myasthenia gravis; neuropathy; myopathy